2011
DOI: 10.1002/pits.20575
|View full text |Cite
|
Sign up to set email alerts
|

Improving Latino, English language learners' reading fluency: The effects of small‐group and one‐on‐one intervention

Abstract: Reading fluency is a critical yet commonly neglected component of early reading instruction. For the large percentage of English language learners (ELLs) who are struggling with or at risk for reading difficulties, there is insufficient research available to help educators implement time‐efficient interventions with these students. Using an experimental design common in field‐based research, the purpose of this study was to evaluate the differential effects of a one‐on‐one (1/1) and small‐group (SG) reading fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 25 publications
4
43
1
1
Order By: Relevance
“…We know of only a small number of other studies (all conducted in the U.S., with English reading materials and assessments) that examined the relative effects of a reading intervention implemented in different student groupings (e.g., Begeny et al 2011;Klubnik and Ardoin 2010;Ross and Begeny 2011;Vaughn et al 2003). In each of those studies, participants benefitted significantly from small-group instruction that was otherwise comparable with one-on-one instruction, and the difference between small-group and one-on-one instruction was negligible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We know of only a small number of other studies (all conducted in the U.S., with English reading materials and assessments) that examined the relative effects of a reading intervention implemented in different student groupings (e.g., Begeny et al 2011;Klubnik and Ardoin 2010;Ross and Begeny 2011;Vaughn et al 2003). In each of those studies, participants benefitted significantly from small-group instruction that was otherwise comparable with one-on-one instruction, and the difference between small-group and one-on-one instruction was negligible.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Klubnik and Ardoin (2010) compared the effectiveness of a reading intervention package administered to English-speaking students individually and in trios and found parallel gains across the treatment conditions. Similarly, Ross and Begeny (2011) compared the effectiveness of a reading fluency intervention delivered individually or in small groups. In this study, participants included six English learners from the U.S.…”
Section: Individual Instruction Compared With Small-group Instructionmentioning
confidence: 99%
“…Although there is substantial evidence for the effectiveness of fluency-based instructional strategies with students whose first language is English, only a small number of studies have evaluated the effects of fluency-based interventions with ELLs (Denton et al 2004;Dufrene and Warzak 2007;Malloy et al 2007;Ross and Begeny 2011). For example, Malloy et al (2007) examined the effects of several reading fluency strategies on five ELLs in grades 1 through 5 and found that students' oral reading fluency improved from interventions such as RR, reinforcement, and error correction.…”
Section: Introductionmentioning
confidence: 99%
“…In an evaluation of one third-grade ELL with reading difficulties, Dufrene and Warzak (2007) found that a combination of modeling and RR strategies modestly improved the student's reading fluency. In a more recent study, Ross and Begeny (2011) evaluated the differential effects of a one-on-one and small group reading fluency intervention, both implemented with five second-grade, Spanish-speaking ELLs and compared to a control condition. Similar to Malloy et al (2007) and Dufrene and Warzak (2007), the fluency-based instructional strategies used by Ross and Begeny included modeling, RR, phrase-drill error correction, and a reward/motivation contingency.…”
Section: Introductionmentioning
confidence: 99%
“…Four of the five students produced ORF gains that were greater than average national growth norms and three students grew more than a half SD on the TOWRE. The researchers indicated that their findings in this study are similar to those of English-only students, and argued that fluency interventions may help ELs as much as English-only students (Ross and Begeny 2011). Due to the design of the study, it is challenging to determine whether the change in student scores were due exclusively to the intervention procedures or a combination of oneto-one and small-group interventions.…”
Section: Fluency Vocabulary and Comprehension Interventionsmentioning
confidence: 87%